A Study on Deformation of Land and Loss of Vegetation Due to Mining at Barapukuria Coal Mine: A Study on Deformation of Land and Loss of Vegetation Due to Mining - Abedin, I.; Abir, M. A. N.; Hussain, A.; Hasan, G. (Journal of Scientific Research, 2019)
Barapukuria coal mine is the biggest coal mine in Bangladesh discovered in 1985. It has lease area around 10.53 square km with the total reserve of 390 million tons. Though it fulfils the major portion of demand of coal in Bangladesh nevertheless it has severe effect like deformation of topography of that surface area while extracting coal from mine and causes severe impact on vegetation on the coal mine vicinity. This is due to some poor design of extraction process. The intent and purpose of this research is to make an analysis of the influence of topography changes due to mining and impact on vegetation. To assess the effect of mining on vegetation and topography remote sensing technology, GIS and Landsat image were used. Our study confirms the deformation of topography and loss of vegetation due to mining. If this mining process continue it will create adverse effect on environment. The result is expected to be a reference for various parties to perform activities related to the mining of coal in Barapukuria coal mine.